Ethical Questions Linked to Rare Diseases and Orphan Drugs – A Systematic Review - Kacetl J; Marešová P; Maskuriy R; Selamat A (Dove Medical Press, 2020)
Jaroslav Kacetl,1 Petra Marešová,2 Raihan Maskuriy,3,4 Ali Selamat5,6 1Department of Linguistics, Faculty of Informatics and Management, University of Hradec Kralove, Hradec Kralove, Czech Republic; 2Department of Economics, Faculty of Informatics and Management, University of Hradec Kralove, Hradec Kralove, Czech Republic; 3Malaysia Japan International Institute of Technology (MJIIT), Universiti Teknologi Malaysia Kuala Lumpur, Kuala Lumpur, Malaysia; 4Department of Architecture, Faculty of Design and Architecture, Universiti Putra Malaysia (UPM), Serdang, Malaysia; 5Media and Games Center of Excellence (MagicX), Universiti Teknologi Malaysia, Skudai, Malaysia; 6School of Computing, Faculty of Engineering, Universiti Teknologi Malaysia (UTM), Skudai, MalaysiaCorrespondence: Petra Marešová Email petra.maresova@uhk.czBackground: Rare or orphan diseases have become an important target of healthcare activities all over the world. The study aims to identify ethical questions linked to rare diseases and orphan drugs and ethical principles or approaches applied to solve them.Methods: Relevant peer-reviewed articles were identified by means of a systematic review. The literature was searched from 20 May 2020 to 20 June 2020. The search included the databases PubMed, Scopus and Web of Science (2010 – April 2020). A total of 4,139 papers related to rare diseases were identified; with 1,205 papers obtained from Scopus; 2,476 papers from PubMed; and 458 from Web of Science with keyword search “ethics” AND “rare” AND “disease”, “ethical” AND “orphan”, “ethical” AND “orphan” AND “drug”, and “ethical” AND “rare“ AND “disease”. Finally, XX studies were chosen for further analysis.Results: The main findings reveal five main ethical issues. The most essential one shows that funding research and development in the field of orphan drugs poses an almost impossible dilemma. Other issues include the significance of non-economic values like compassion and beneficence in decision-making related to orphan drugs and rare diseases; the identification of limits to labelling diseases as rare; barriers to global, supranational and international cooperation; and last but not least, determining and establishing panels of decision-makers.Conclusions: A strictly global approach would be the most appropriate way to deal with rare diseases. Nonetheless, international, let alone global, cooperation seems to be completely beyond the reach of the current international community, although the EU, for instance, has a centralized procedure for labelling orphan drugs. This deficit in international cooperation can be partly explained by the fact that the current technologically globalized world still lacks globally accepted ethical values and rules. This is further aggravated by unresolved international and intercultural conflicts. In addition, the sub-interests of various parties as well as the lack of desire to deal with other people’s problems need to be taken into account. The aforementioned problems are difficult to avoid. Nevertheless, let us be cautiously optimistic. At least, there are people who raise ethical questions about rare diseases and orphan drugs.Keywords: ethical aspects, ethical principles, rare disease, orphan drugs